Localisation of aluminium by histochemical and electron probe x-ray microanalytical techniques in bone tissue of cases of renal osteodystrophy. Issue 11 (November 1982) - Smith, P S; McClure, J
Abstract : Histochemical studies and electron probe x-ray microanalysis for aluminium have been performed on 16 samples of undecalcified bone from cases of renal osteodystrophy associated with a syndrome suggestive of dialysis encephalopathy (five cases), age and sex matched controls for these and a group of patients with chronic renal failure (six cases) who have never been on haemodialysis. Aluminium was detected only in the patients with a dialysis encephalopathy-like syndrome. This group had significant histological bone disease the features of which were broadly consistent with the so-called atypical renal osteomalacia which is thought to be due to a metal toxin. Aluminium was demonstrated at the interface between osteoid and mineralised tissue–that is, at the site of the calcification front, where it could interfere with the mineralisation process. In the group of patients who had never been subjected to haemodialysis there was also significant histological bone disease but no evidence of aluminium accumulation. In this group the bone disease was of a more typical pattern of osteomalacic changes coupled with those of hyperparathyroidism.